Extraction of Nickel Oxide from Spent Catalyst for Environmentally Safe Disposal - Ibraheem, Fakhri H.; Mahmoud, Heaven E.; Salih, Dunya I.; Smail, Jahfar M.; Karim, Hawbash H.; Chaqmaqchee, Faten A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Molecular sieves are used in various industries, especially petroleum and gas processing plants, as catalysts. These materials are in contact with crude oil products. After several operational years, these materials’ activities were reduced to a nonfeasible level called spent molecular sieve. Tens of tons are disposed of annually from oil and gas companies in Iraq. The paper aims to determine the kinds and amounts of toxic materials carried by the nickel oxide sulfur bed spent catalyst and then submit the suitable treatment methods, such as leaching by water, base solution, and acid solution. Aradioactive test was first done to ensure the material was free from the radioactivity array. The material was tested for nickel oxide concentration after each step of treatment. It was found that the leaching by water reduces the content by 4.5% during 24 h of leaching and 15.5% after 7 days. The leaching by alkaline sodium hydroxide 10% concentration solution reduces the content by 7% during 24 h and 14.3% after 7 days. The 10% hydrochloric acid concentration solution leaching reduces the nickel content by 10.8 during 24 h and 65.7 after 7 days. Leaching by acid solution is more efficient in the extraction of nickel oxide. The treatment method novelty is to be carried out at reasonable temperatures with high metal extraction efficiency. The research results achieved this goal of attaining extraction at an easily achievable temperature of 70°C with a relatively good extraction rate higher than 65%.